Temperature Measurement-Inquiry-Based Learning Activities for Third Graders - Žaneta Gerhátová; Peter Perichta; Marián Drienovský; Marián Palcut (MDPI AG, 2021)
The article presents our Inquiry-Based Learning (IBL) activities in the project-based Science education of third graders (8-9-year-old pupils) in the Slovak Republic. Individual tasks of project assignment titled "Temperature Measurement" were conceived for "guided inquiry". We also supported the IBL of pupils by interactive education strategy-Integrated e-Learning (INTe-L). The strategy was built on the role of interactive simulations and experimenting at the knowledge acquisition. The following INTe-L components were used: (a) on-site and remote experiments, (b) interactive simulations and (c) electronic study materials. The research was based the hypothesis that the project-based teaching of the topic "Temperature Measurement" using the IBL activities is significantly more efficient than traditional (instructivist) way of teaching. To verify the hypothesis, we carried out a pedagogical experiment on a sample of 60 respondents. The third graders were divided into two parallel groups: an experimental group (EG, 30 pupils) and control group (CG, 30 pupils). To get a relevant feedback, pre-test and post-test were developed and applied. The results attained in the EG were statistically processed, evaluated, and subsequently compared with those in the CG. The analysis of the results attained by the EG showed that their knowledge acquisition has been increased by 24% compared to CG. We have created a methodology for making simple scientific project assignments with the implementation of all components of the new integrated e-learning education strategy (real and real remote experiment, e-simulation, e-learning material). On a specific example of the topic "Temperature Measurement" in primary education, we have presented the possibility of using a "guided inquiry" in the implementation of individual experimental tasks. We have introduced a form of teamwork that allows to harmonize the teaching requirements with individual learning approach and helps to prepare pupils for planned work and independent knowledge acquisition and problem solving. The study has shown that complex IBL activities can be successfully applied at primary school 3rd grade level already. Our form of education with the wider use of modern information and communication technologies (ICT) was attractive for the learners and helped them to develop interdisciplinary relationships. The integrated e-learning has helped third grades to develop a deeper conceptual understanding of temperature and allowed them to prepare presentations to demonstrate their conceptual knowledge. The approach allowed pupils to gain key competencies in Science (discussion and presentation of results). It has also increased the pupils' interest in Science in general and helped them to understand links between different subjects.